Parámetros bióticos y abióticos en estanques de pesca subtropicales - Millan, Rodrigo Ney [UNESP]; Sipaúba-Tavares, Lúcia Helena [UNESP] (My University, 2014)
This study was conducted to evaluate the plankton communities and water quality at a fee-fishing farm over a 1-year period. Samples for the determination of biotic and abiotic variables were collected monthly during the study year. Water samples were collected at 7 sampling sites: inlet water, wetland, fishponds (3 sites), soil filter system and outlet water. The temperature, dissolved oxygen, pH and nutrients were measured. A similarity analysis for plankton densities and nutrients detected 4 groups of sites. The outlet water site differed markedly from the other sites. Higher nitrate and nitrite concentrations were observed at the inlet water and wetland sites in association with species belonging to the Bacillariophyceae, Cyanobacteria and Zygnemaphyceae. Fishpond sites 2 and 3 were associated with species belonging to the Chlorophyceae and with variables such as temperature, dissolved oxygen and pH. Zooplankton communities were most distinctive in the soil filter system. Rotifers were the most representative group among the zooplankton communities. The results demonstrated that plankton communities and abiotic variables were affected by water flow and by animals in the neighbouring areas. The soil filter system at the effluent of the fee-fishing farm was found to be an important tool, suitable for adoption in aquaculture systems to improve outlet water quality.
Biotic and abiotic parameters at a subtropical fee-fishing farm
Keywords: Fish-ponds; Limnology; Physical and chemical parameters; Phytoplankton; Zooplankton